Contemporary Bioethics: Islamic Perspective - Al-Bar, Mohammad Ali (Springer, 2015)
This book discusses the common principles of morality and ethics derived from divinely endowed intuitive reason through the creation of al-fitr' a (nature) and human intellect (al-‘aql). Biomedical topics are presented and ethical issues related to topics such as genetic testing, assisted reproduction and organ transplantation are discussed.